Delivering Remote Learning Using a Low-Tech Solution: Evidence from a Randomized Controlled Trial in Bangladesh - Liang Choon Wang; Michael Vlassopoulos; Asad Islam; Hashibul Hassan (Institute of Labor Economics (IZA), 2023)
The Covid-19 pandemic caused prolonged school closures worldwide. Children in resource- poor settings were particularly affected given their limited access to remedial distance learning opportunities through the internet, television, and radio. To address the poor access to formal education, we designed an educational intervention consisting of a set of audio lessons that were delivered through mobile phones to primary school students using Interactive Voice Response (IVR). During the 15-week program period, parents could access the lessons for free by calling a designated phone number and listening to a lesson with their child at any time. We delivered the randomized intervention to 1,763 primary school children across 90 villages in Bangladesh during the 2021 Covid-19 school closures. The intervention improved the test scores of children in literacy and numeracy by 0.60 Standard Deviations (SD). Additionally, the intervention led to an increase in the amount of time that parents spent on homeschooling. The intervention was particularly beneficial for academically weaker students, those from the poorest strata, and those with less-educated caregivers. Our results suggest that this scalable and low-cost intervention could be leveraged in similar settings to address learning losses of marginalized students.
Keywords: C93; I21; I24; 330; school closures; remote education; Interactive Voice Response (IVR); COVID-19; randomized controlled trial; Bangladesh